PENERAPAN FUZZY-QUERY DATABASE PADA SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN BEASISWA - Anwar, Khoerul; Gunawan, Ario (DINAMIKA DOTCOM, 2011)
The determination of scholarship recipients with several requirements of several types of scholarships offered is often a constraint in membangaun Decision Support System that can assist the student in determining a student who could be recommended to get a scholarship. This study aims to obtain scholarship recipients to perform database queries using a combination of fuzzy logic and query the database (Fuzzy-Query). The combination of these two methods are new methods that could become an alternative method in building database processing. The results obtained from the fuzzy-Quey method can minimize the selection of scholarship acceptance.. Â Keywords: fuzzy logic, membership function, firestrength, fuzzy database query.